Operation of large-volume cubic press above 8 GPa and 2500°C with a centimeter-sized cell volume using an optimized hybrid assembly - Song, Guozhu; Ma, Dejiang; Zhou, Xuefeng; Wang, Lingfei; Wei, Zheng; Xu, Chao; Wang, Wendan; Wang, Liping; Zhao, Yusheng; Wang, Shanmin (High pressure research, 2021)
Large-volume cubic presses are widely used in scientific research and industrial applications. However, their pressure capability is often limited to 6 GPa, which severely restricts their applications under extended pressures. In this work, we report a newly designed hybrid cell assembly for cubic presses by embedding six WC pressure-enhancing blocks into the pyrophyllite pressure-transmitting medium, leading to profoundly increased pressure efficiency (i.e. more than 40%), hence largely extended pressure conditions up to 8-9 GPa without sacrificing sample volume. Because of the optimized design, the expensive first-stage WC anvils are effectively protected, which makes the press routinely operated up to 8-9 GPa in avoiding damage of anvils. Through optimization of heating efficiency, temperature of the new assembly can reach above 2500°C. Using this high pressure cell, we have synthesized centimetre-sized polycrystalline cubic BN bulk sample by the direct transformation of hexagonal BN at 7.7 GPa and 2000°C. Successful implementation of large-volume cubic press up to 8-9 GPa and 2500°C would provide many opportunities for the synthesis of new materials on massive scale (e.g. novel superhard compounds) and for the study of materials at extended pressures.